DETERMINAN FACTORS OF EMPLOYEE ENGAGEMENT GENERASI Y - Nelmida, Nelmida (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- The purpose of this study was to determine the determinant factors of employee engagement in insurance companies. Design/methodology/approach- The population of the study amounted to 285 people with techniques to determine the number of samples using a purposive sampling technique of 109 people. Data collection techniques using questionnaires with the analysis method used Smart PLS (Partial Least Square). Findings- Based on the analysis found that management style has a positive effect on employee engagement, remuneration, the opportunity for skill enhancement, and the work environment does not affect employee engagement. Limitation- The study has several limitations, namely the scope of the study is still small so the number of samples used is small, as a result, the results of this the study can not be generalized, and the number of independent variables used in this study is only 4 variables, while many factors affect employee engagement. This research implies that it can be used as input in taking the policy, especially about management style. Keywords: Gen-Y, employee engagement, Smart-PLS,